1111 INTACT FIBROBLAST GROWTH FACTOR 23 TESTED BY A FULLY AUTOMATED ASSAY: CLINICAL CORRELATES AND PROGNOSTIC VALUE IN CHRONIC SYSTOLIC HEART FAILURE. (15th December 2022) - Vergaro, Giuseppe; Castiglione, Vincenzo; Del Franco, AnnaMaria; Gentile, Francesco; Aimo, Alberto; Saponaro, Federica; Masotti, Silvia; Prontera, Concetta; Fusari, Niccolò; Emdin, Michele; Passino, Claudio
Abstract: Background and aims: Fibroblast growth factor-23 (FGF23) has been associated with left ventricular (LV) hypertrophy, fibrosis, and heart failure (HF). We aimed to investigate the clinical correlates and prognostic value of intact FGF23 (iFGF23) in HF patients. Methods: Patients with systolic HF (left ventricular ejection fraction – LVEF <50%) were prospectively enrolled. iFGF23 was tested with a fully automated immuno-chemiluminescent assay. Patients were divided into iFGF23 tertiles and followed-up for all-cause death, cardiac death, and the composite of all-cause death and HF hospitalizations. Results: We enrolled 150 patients (82% males; median age 65 years). First, second, and third iFGF23 tertiles were <35.2 pg/mL, 35.2-50.9 pg/mL, and >50.9 pg/mL. Patients in the upper iFGF23 tertile had lower LVEF (p=0.014), higher N-terminal pro-B-type natriuretic peptide (NT-proBNP, p=0.001), and lower peak VO2 (p<0.001). Plasma phosphate, estimated glomerular filtration rate (eGFR), and LV mass index were independently associated with higher iFGF23 levels (all p<0.05). Patients in the upper tertile were at higher risk of all-cause death (p=0.001), cardiac death (p=0.001), and of the composite of all-cause death and HF hospitalizations (p=0.003). iFGF-23 was an independent predictor of all the endpoints after adjustment for age, LVEF, eGFR, and NT-proBNP. Conclusions: Circulating iFGF23 is associated with renal dysfunction, disease severity and outcome in systolic HF. Figure. Prognostic impact of FGF23 levels in patients with systolic heart failure (HF). In a cohort of HF patients with systolic dysfunction, higher iFGF23 levels (marker of increased cardiac fibrosis and hypertrophy) were associated with a more severe disease, as expressed by lower left ventricular systolic function, higher circulating levels of N-terminal pro-B-type natriuretic peptide (NT-proBNP), lower oxygen consumption at cardiopulmonary exercise test and worse renal function. Moreover, iFGF23 elevation identified patients at higher risk for all-cause and cardiac mortality, and HF hospitalization.